A Comprehensive Molecular Analysis of in Vivo Isolated EpCAM-Positive Circulating Tumor Cells in Breast Cancer. (28th July 2021) - Strati, Areti; Zavridou, Martha; Kallergi, Galatea; Politaki, Eleni; Kuske, Andra; Gorges, Tobias M; Riethdorf, Sabine; Joosse, Simon A; Koch, Claudia; Bohnen, Anna-Lena; Mueller, Volkmar; Koutsodontis, George; et al.
Abstract: Background: Circulating tumor cell (CTC) analysis is highly promising for liquid biopsy-based molecular diagnostics. We undertook a comprehensive molecular analysis of in vivo isolated CTCs in breast cancer (BrCa). Methods: In vivo isolated CTCs from 42 patients with early and 23 patients with metastatic breast cancer (MBC) were prospectively collected and analyzed for gene expression, DNA mutations, and DNA methylation before and after treatment. 19 healthy donor (HD) samples were analyzed as a control group. In identical blood draws, CTCs were enumerated using CellSearch ® and characterized by direct IF staining. Results: All 19 HD samples were negative for CK8, CK18, CK19, ERBB2, TWIST1, VEGF, ESR1, PR, and EGFR expression, while CD44, CD24, ALDH1, VIM, and CDH2 expression was normalized to B2M (reference gene). At least one gene was expressed in 23/42 (54.8%) and 8/13 (61.5%) CTCs in early BrCa before and after therapy, and in 20/23 (87.0%) and 5/7 (71.4%) MBC before and after the first cycle of therapy. PIK3CA mutations were detected in 11/42 (26.2%) and 3/13 (23.1%) in vivo isolated CTCs in early BrCa before and after therapy, and in 11/23 (47.8%) and 2/7 (28.6%) MBC, respectively. ESR1 methylation was detected in 5/32 (15.7%) and 1/10 (10.0%) CTCs in early BrCa before and after therapy, and in 3/15(20.0%) MBC before the first line of therapy. The comprehensive molecular analysis of CTC revealed a higher sensitivity in relation to CellSearch or IF staining when based on creatine kinase selection. Conclusions: In vivo-CTC isolation in combination with a comprehensive molecular analysis at the gene expression, DNA mutation, and DNA methylation level comprises a highly powerful approach for molecular diagnostic applications using CTCs.